Lebanese Women's Fiction - Aghacy, Samira (2001)
This study undertakes an examination of Lebanese women's fiction over the past forty years or so. For many women, the urban environment is an escape from the restrictive traditional community that is closely aligned with a rural mentality. Many of these writers tend to see the city in stark contrast to the country, which, in their eyes represents restraining cultural values. If in some cases the city and the country are represented as real, tangible places, the majority of women tend to view them as “states of mind and feeling”1 or as representations. Some female writers see the city and the village in ontological opposition between repression and freedom, backwardness and progress, and past and present—or, as Raymond Williams refers to it, “of consciousness with ignorance; of vitality with routine; of the present and actual with the past or the lost.”2 Nevertheless, it is clear that in many cases the city incorporates and embraces both the traditional and modern patterns, because “an old order, a ‘traditional' society, keeps appearing, reappearing, at bewilderingly various dates.”3 Far from viewing themselves as alienated and degraded beings in the corrupt and hellish city4 or the modern wasteland, women see the nurturing city as a symbol of well-being, independence, and freedom from shackles. Indeed, they become so immersed in city life that, for some of them, there is “little reality in any other mode of life.”5 The city gives them the opportunity to escape the narrow confines of home, family, and stifling traditions that have relegated them to a corner and associated them with a nostalgic past. Accordingly, for many of them, the city has become, as Williams puts it, “the physical embodiment of a decisive modern consciousness,”6 a place consistently in flux and motion7 where women attempt to keep the ever-haunting past at bay and reveal a thrust for change and for experience and knowledge that they try to replenish in the city.